2004
DOI: 10.1016/j.beproc.2004.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Behavior-analytic approaches to decision making

Abstract: Behavior analysis has much to offer the study of phenomena in the area of judgement and decision making. We review several research areas that should continue to profit from a behavior-analytic approach, including the relative merit of contingency-based and rulegoverned instruction of solving algebra and analogy problems, and the role of conditioned reinforcement and the inter-trial interval in a type of Prisoner's Dilemma game. We focus on two additional areas: (1) the study of base-rate neglect, a notorious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…Perhaps this is a result of cognitive factors resulting from a lifetime of learning, a conclusion consistent with species differences in other areas of decision-making (e.g. Fantino, 2004). Despite these differences across studies, budget has been shown, in at least some studies, to have a similar influence and evidence suggests that discriminative stimuli may also influence both human and nonhuman risky choice.…”
Section: Choosing Between Certain and Variable Outcomesmentioning
confidence: 85%
See 1 more Smart Citation
“…Perhaps this is a result of cognitive factors resulting from a lifetime of learning, a conclusion consistent with species differences in other areas of decision-making (e.g. Fantino, 2004). Despite these differences across studies, budget has been shown, in at least some studies, to have a similar influence and evidence suggests that discriminative stimuli may also influence both human and nonhuman risky choice.…”
Section: Choosing Between Certain and Variable Outcomesmentioning
confidence: 85%
“…For example, the recent literature on human judgement and decision-making is replete with examples of nonoptimal and/or illogical decisions (e.g. Fantino, 1998Fantino, , 2004, one of which, the sunk-cost effect, will be discussed later as an example of behavioural persistence. In most cases, choices become more optimal under conditions in which the true contingencies and probabilities governing the outcomes are made more transparent.…”
Section: Introductionmentioning
confidence: 98%
“…A similar finding was reported by Wiklund (1990) in a study of brood defense by merlins, a kind of raptor. Fantino (2004) gave a similar task to college students and to pigeons. Both subject groups were rewarded (with money or food) for pressing a computer keyboard an undetermined number of times until the screen flashed an award.…”
Section: Individual Psychology and Social Sustainability: The Sunk Comentioning
confidence: 91%
“…In terms of the distinction suggested by Fantino (2004), the above scenario with humans involves "resource allocation", as opposed to "continuing-to-invest" in which participants are asked whether they wish to invest further money or time in a losing venture. The first study to demonstrate the sunk cost effect in nonhuman animals, was reported by Navarro and Fantino (2005) and was analogous to a continuing-to-invest problem.…”
Section: The Sunk Cost Effect In Pigeonsmentioning
confidence: 99%